2020
DOI: 10.1007/s11663-020-01853-5
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning for Robust Target Prediction in a Basic Oxygen Furnace System

Abstract: The steel-making process in a Basic Oxygen Furnace (BOF) must meet a combination of target values such as the final melt temperature and upper limits of the carbon and phosphorus content of the final melt with minimum material loss. An optimal blow end time (cut-off point), where these targets are met, often relies on the experience and skill of the operators who control the process, using both collected sensor readings and an implicit understanding of how the process develops. If the precision of hitting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Using additional sensors such as these improve prediction accuracy, and may also extend process understanding, but still lacks the transparency to explain influential factors of the collected data. In our previous research, we compared the prediction accuracy between several conventional ML algorithms, trained on a full-variance data set that includes all types of heats from years of production [1]. We found that many earlier publications use limited data sets with a lower variance in the training examples and the target outcomes.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Using additional sensors such as these improve prediction accuracy, and may also extend process understanding, but still lacks the transparency to explain influential factors of the collected data. In our previous research, we compared the prediction accuracy between several conventional ML algorithms, trained on a full-variance data set that includes all types of heats from years of production [1]. We found that many earlier publications use limited data sets with a lower variance in the training examples and the target outcomes.…”
Section: Related Workmentioning
confidence: 99%
“…Some conventional ML algorithms are relatively good at explaining model predictions, such as decision trees, k-nearest neighbours. These have been used for temperature prediction in BOF-processes, but with a less satisfactory result [1]. Further, machine learning models that are often considered as easy to interpret, such as linear regression and decision trees, may still be impossible for humans to interpret when the data is high dimensional [18].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The end-point phosphorus (P) content is one of the main end-point targets in steelmaking process due to its significant influence on steel products. 1,2) With the increasing demand for low and ultra-low phosphorus steels, many steel plants apply high-efficiency dephosphorization technology into converter. 3,4) However, in view of the fact that most process parameters are correlative with each other, it is difficult to control the end-point phosphorus content in a high accuracy degree, and thus numerous researches have been carried out to realize the precise control of the end-point P content through the mathematical and intelligent models.…”
Section: Introductionmentioning
confidence: 99%
“…The impurities such as phosphorus should be kept under control in the steelmaking process due to their possible adverse effects on the steel quality. [1] Thus, the endpoint phosphorus (P) content is one of the main target values at the end of smelting operation in the steelmaking process due to its significant influence on the steel products, [2][3][4][5] particularly for low phosphorous steels production. To enhance the dephosphorization efficiency, a lot of industrial experiment is carried out to determine the optimal parameters.…”
mentioning
confidence: 99%